Identification of the most profitable combination of breed-type and management system for smallholder dairy cattle keepers in Senegal - CGIAR Research Program on Livestock (2020)
Stage is end of research. The most profitable combination of breed-type and management system for smallholder dairy cattle keepers in Senegal has been identified. The next stage is to promote piloting of this breed-type and management system, through working with the public and private sectors.